2017
DOI: 10.1007/s00296-017-3783-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-synonymous WNT16 polymorphisms alleles are associated with different osteoarthritis phenotypes

Abstract: Hereditary factors have a strong influence on osteoarthritis (OA). The Wnt pathway is involved in bone and cartilage homeostasis. Hence, we hypothesized that allelic variations of WNT16 could influence the OA phenotype. We studied 509 Caucasian patients undergoing joint replacement due to severe primary OA. Radiographs were used to classify the OA as atrophic or hypertrophic. Two nonsynonymous polymorphisms of WNT16 (rs2707466 and rs2908004) were analyzed. The association between the genotypes and the OA pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…Radiographic OA was associated with high BMD and increased rate of bone loss . WNT16 rs2908004 polymorphism was associated with different OA phenotypes (atrophic or hypertrophic) . Our results indicate WNT16 rs2908004 polymorphism conferred susceptibility to OA by comparing genotype and allele distribution between cases and controls.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Radiographic OA was associated with high BMD and increased rate of bone loss . WNT16 rs2908004 polymorphism was associated with different OA phenotypes (atrophic or hypertrophic) . Our results indicate WNT16 rs2908004 polymorphism conferred susceptibility to OA by comparing genotype and allele distribution between cases and controls.…”
Section: Discussionmentioning
confidence: 66%
“…We selected five SNPs (DVL1 rs61735963, WNT16 rs2908004, ITIH5 rs10795550, LRP1 rs1799986 and SFRP1 rs1127379) and investigated their association with OA risk in a Chinese population. Two SNPs (WNT16 rs2908004 and LRP1 rs1799986) were reported . WNT16 could influence bone mineral density (BMD), cortical bone thickness and osteoporotic fracture risk .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While previous work indicated that there was no association between Wnt16 gene polymorphisms and osteoarthritis (OA) ( 90 ), recently, two SNPs of the Wnt16 gene (rs2707466 and rs2908004) known to be associated with BMD have been implicated in the hip and knee OA phenotypes in Caucasian patients in a sex-dependent manner ( 91 ). This report was the first to suggest the involvement of the Wnt pathway in determining the OA phenotypes.…”
Section: Wnt16 In Osteoarthritis Pathogenesismentioning
confidence: 99%
“…В настоящее время определены генетические факторы, которые играют важную роль в патогенезе различных остеоартрозов, например: пол (остеоартритом чаще страдают женщины); наследственная артроофтальмопатия (синдром Стиклера, при котором имеется мутация гена COL2A1, или гена COL11A2); различные наследственные патологические состояния и/или заболевания суставов и костей (гипермобильный синдром, различные дисплазии и др. ); этниче-ская принадлежность пациентов [2,8,15], однако изучение влияния генетических факторов в развитии вторичных остеоартрозов (диспластический, ревматоидный, подагрический) единичны и практически отсутствуют при идиопатическом коксартрозе [5,12], что и явилось целью нашей работы.…”
Section: генетические аспекты развития коксартрозаunclassified